An Optimized and Versatile Counter-Flow Centrifugal Elutriation Workflow to Obtain Synchronized Eukaryotic Cells - Liu, Yongqiang; Nan, Bei; Niu, Junhua; Kapler, Geoffrey M.; Gao, Shan (Frontiers in Cell and Developmental Biology, 2021)
Cell synchronization is a powerful tool to understand cell cycle events and its regulatory mechanisms. Counter-flow centrifugal elutriation (CCE) is a more generally desirable method to synchronize cells because it does not significantly alter cell behavior and/or cell cycle progression, however, adjusting specific parameters in a cell type/equipment-dependent manner can be challenging. In this paper, we used the unicellular eukaryotic model organism, Tetrahymena thermophila as a testing system for optimizing CCE workflow. Firstly, flow cytometry conditions were identified that reduced nuclei adhesion and improved the assessment of cell cycle stage. We then systematically examined how to achieve the optimal conditions for three critical factors affecting the outcome of CCE, including loading flow rate, collection flow rate and collection volume. Using our optimized workflow, we obtained a large population of highly synchronous G1-phase Tetrahymena as measured by 5-ethynyl-2'-deoxyuridine (EdU) incorporation into nascent DNA strands, bulk DNA content changes by flow cytometry, and cell cycle progression by light microscopy. This detailed protocol can be easily adapted to synchronize other eukaryotic cells.